Pemanfaatan Sampah Rumah Tangga Di Desa Bargot Topong Kecamatan Batang Angkola Kabupaten Tapanuli Selatan Provinsi Sumatera Utara - Siregar, Esli Zuraidah; Harahap, Nurintan Muliani; Hasibuan, Nurharisyah; Harahap, Aisyah Budi; Ritonga, Anas Habibi; Harahap, Masrul Efendi Umar (Kifah: Jurnal Pengabdian Masyarakat, 2023)
Abstract : The implementation of community service activities is motivated by the awareness and behavior of people who still do not care about environmental cleanliness. This PKM aims to provide education to the Bargot Topong community about waste management to reduce environmental pollution that occurs. The PKM method used is three stages, namely problem mapping, counseling and mentoring. The results of the activity show that before the PKM activity, the community did not know the types of household waste well, public awareness to protect the environment was still low. But after PKM activities were carried out, the community already understood the types of waste and how to classify waste based on the type of waste. As well as knowing the types of waste that can be recycled to produce organic fertilizer and can be used as skills that can be reused.